Enhancement of piezoelectric energy harvester power density using natural rubber - Muhamad L.; Salleh H. (Institute of Electrical and Electronics Engineers Inc., 2023)
Ferroelectric ceramics; Latexes; Lead zirconate titanate; Rubber; Rubber additions; brittle; Electronic device; Energy harvesting systems; enhance; increase; Piezoelectric energy harvesters; vibration; Vibration-based energy harvesting; Energy harvesting